Degressive proportionality in the context of the composition of the European Parliament - Cegiełka, Katarzyna; Dniestrzański, Piotr; Łyko, Janusz; Misztal, Andrzej (Degresywna proporcjonalność w kontekście składu Parlamentu Europejskiego, 2011)
The European Union, despite many attempts, has yet to devise a precisely determined algorithm of appointing the composition of the Parliament – it is only known that the algorithm must be consistent with the generally understood degressive proportionality. In the article the authors look at the history of the problem and analyse selected papers on this subject, along with the results of their own research
Ekonomia = Economics, 2011, Nr 2 (14), s. 95-105
Keywords: degressive proportionality; indivisible goods; the European Parliament